Efeitos nas propriedades mecânicas, elásticas e de deformação em concretos com altos teores de escória e cinza volante - Beck, Sílvio Maurício (2009)
The use of byproducts and industrial waste as pozzolanic, is an alternative to achieve the sustainability, economy and durability in concrete structures. This survey has as its purpose to analyze the effect on mechanical, elastic and deformation properties on concrete with a high level of granulated slag from blast furnace and fly ash in place of Portland bulk cement. The use of high levels of mineral additions has the purpose of increasing the durability and reducing the consumption of cement, the use of hydrated lime aims to activating these adittions, restore part of the calcium hydroxide consumed by the pozzolanic reactions, increasing the initial and final strength to the mixtures. This way, three mixtures of concrete have been studied: one of them without mineral additions, only using Portland cement (CP V-ARI), taken as a control, with relations a/c 0.40, 0.60 and 0.83, and two mixtures with mineral additions in place of cement in equal mass, with 70% of slag and 20% of fly ash, being one of them with addition of 20% of hydrated lime on the mass of binders in addition to the cement, both to the relations a/mc 0.30/0.33, 0.40 and 0.49, which have been renamed as R, EV and EVC. Tests were held to resistance to axial compression in bodies of evidence (10x20cm) the ages of 07 28, 91 and 300 days, whose results range from 18.2 MPa and 81 MPa, tests of resistance to traction by diametral compression and module of elasticity at 28, 91 and 300 days, as well as tests of total shrinkage on prismatic bodies of evidence (10x10x30 cm) at 28, 91, 180 and 300 days. The results of mechanical, elastic and strain resistance have been also correlated with some intervening and independent variables, as well as some existing regulatory requirements. The results have been analyzed to each trace individually, in relation to the control traces, in relation to the evolution of the resistance, effectiveness of the use of the hydrated lime and in equal relationship a/mc 0.4. In the analysis of the equal relationship a/mc 0.400, in the case of reference concrete, in the initial age, the resistance to the axial compression of the concrete EV was, in media, 72% of the one presented by it, being the resistance to the EVC 55%, and in the final age, 65% and 50% respectively. In the case of the traction by diametral compression, to 28 days the concrete EV presented 76% of the resistance of the reference, and the concrete EVC 58%. This relation to 300 days was 80% and 61% respectively. To the elasticity module, to 28 days, the concrete EV presented 82% and the EVC 70% of the result obtained by the reference mixture, maintaining this proportion until the final age (300 days). In the analysis of the total retraction, the concrete EV presented an inferior retraction 10% inferior to the reference trace, while the concrete EVC to 300 days presents a good retraction 16% superior to it. The observation through the conjuncture of the results found shows a satisfactory relation among the different traces studied, making feasible the use of high levels of mineral additions in substitution to the large portion of cement in bulk.